Optimizing the Use of Android-Based Audio Visual Integrated System (AVIS) Application in Theory Exam of Driving License Service by Traffic Unit of Cimahi Resort Police - Christanto, Fery Afrilio; Chairul Muriman Setyabudi (HM Publisher, 2023)
The innovation of the android-based audio visual integrated system (AVIS) online limited area application by the Cimahi police resort, which is relatively new, still requires a lot of improvement and refinement. This study aimed to determine the use of the Android-based limited area online AVIS application and how to optimizing of the AVIS application. This research was conducted with a qualitative approach, using descriptive analysis research methods, as well as data collection techniques by interviewing, observing, and document review. The study found that the use of AVIS application based on components of the law, facilities, infrastructure, internal control, and performance evaluation of executors has not met the standards. Influencing factors, namely innovation, communication channels, and social systems, are inhibiting factors. In conclusion, optimizing the use of the android-based limited area AVIS online application in the SIM theory test service by the Cimahi Police Traffic Unit based on the Public Service Improvement Theory by Kearns (2010) can be done through 4 strategies, namely growth strategy, efficiency increasing strategy, stability strategy, and collaboration strategy.